Model Stokastik Pada Penyebaran Penyakit Tuberkulosis - Aziezah, Nur; Sumarno, Hadi; Jaharuddin, Jaharuddin (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2024)
Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis. This disease represents a significant global public health challenge. Consequently, a stochastic differential equation model of tuberculosis has been developed. In this context, an analysis examines the impact of complete treatment on the disease-free population distribution, duration of disease-free status, and the probability of remaining disease-free. The analysis shows that as the rate of complete treatment increases, the probability of achieving disease-free status rises, the duration of remaining disease-free shortens, and the number of disease-free individuals grows over time. Keywords: Complete Treatment, Disease-Free Duration, Stochastic Differential Equations, Tuberculosis